How do International Students Reconstruct their Identity as Readers when they Transition into Canadian Post-Secondary Education? - Chen, Danni; Hanson, Aubrey Jean (Language and Literacy / Langue et littératie, 2023)
Recognizing the cultural transitions Chinese international students undergo as readers in the Canadian higher education system, this study explores the difficulties encountered by four Chinese students and uncovers how they experienced, responded to, and transformed in a new cultural reading environment. Focusing on the notion of a reader’s identity, this study uses narrative inquiry to show how participants’ readers identities are reconstructed in a new cultural reading environment. It concludes that readers’ identities reflect readers’ different cultural memberships. As international students crossing cultural boundaries, their identities as readers shape how they interpret and understand the meaning of reading materials.